THE NEED OF INFORMATION TECHNOLOGY ON THE PROFESSIONAL INTEREST AND PROFESSIONAL ASPIRATIONS OF STUDENTS STUDYING AT HIGHER SECONDARY LEVEL. - Lipika Raj; Saxena, Deepshikha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Aspiration is the normal reaction of a human being through which a human being is eager to acquire knowledge. Different people have different aspirations based on different experiences. Applied research has emphasized the impact of information technology on professional aspirations, in which the training given in ICT and Polytechnic etc. is important. The present era is the era of communication and technology, due to the use of which the whole world has turned into a village. The contribution of information technology has become very important in all the fields of education, military, business, medicine and research. Keeping in view the demand and utility of modern times, the attitude of students and their aspirations can be developed through interesting information technology and vocational education. Students are the future of the country and build the nation. Quality educational development can be made effective by making students aware of new technology knowledge and information which makes students mature for future life on the global stage. It is certainly possible that in the near future the medium of teaching will depend on information technology instead of paper.